2019
DOI: 10.1515/bot-2018-0114
|View full text |Cite
|
Sign up to set email alerts
|

A conspectus of the filamentous marine fungi of Sweden

Abstract: Marine filamentous fungi have been little studied in Sweden, which is remarkable given the depth and width of mycological studies in the country since the time of Elias Fries. Seventy-four marine fungi are listed for Sweden based on historical records and recent collections, of which 16 are new records for the country. New records for the country are based on morphological identification of species mainly from marine wood, and most of them from the Swedish West Coast. In some instances, the identifications hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Bohuslän, Öland, Skåne, (Henningsson 1974 , as Culcitalna achraspora ≡ Trichocladium achrasporum as a sexual morph). Uppland (Tibell et al 2019 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Bohuslän, Öland, Skåne, (Henningsson 1974 , as Culcitalna achraspora ≡ Trichocladium achrasporum as a sexual morph). Uppland (Tibell et al 2019 ).…”
mentioning
confidence: 99%
“…Note . Originally described from Sweden, this is a species mostly collected on land plants, but only recently (Tibell et al 2019 ) observed from marine wood. Eight marine Neocamarosporium species are listed in the website http://www.marinefungi.org , often from salt marsh plants such as Halimione portulacoides, Salicornia spp., while N. endophyticum was described from Zostera noltii .…”
mentioning
confidence: 99%
See 3 more Smart Citations